Outcomes of patients with and without baseline lipid-lowering therapy undergoing revascularization for left main coronary artery disease: analysis from the EXCEL trial. Issue 2 (March 2019) - Chen, Shmuel; Redfors, Björn; Liu, Yangbo; Vrolix, Mathias; Macaya, Carlos; Ben-Yehuda, Ori; Kappetein, Arie Pieter; Sabik, Joseph F.; Serruys, Patrick W.; Stone, Gregg W.
Abstract : Objectives: There is a paucity of data on the effect of baseline lipid-lowering therapy (LLT) in patients undergoing revascularization for left main (LM) coronary artery disease (CAD). We compared outcomes for patients with LMCAD randomized to percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) according to the presence of baseline LLT in the EXCEL trial. Patients and methods: The EXCEL trial randomized 1905 patients with LMCAD and SYNTAX scores up to 32 to PCI with everolimus-eluting stents versus CABG. Patients were categorized according to whether they were medically treated with LLT at baseline, and their outcomes were examined using multivariable Cox proportional hazards regression. The primary endpoint was a composite of death, stroke, or myocardial infarction at 3 years. Results: Among 1901 patients with known baseline LLT status, 1331 (70.0%) were medically treated with LLT at baseline. There were no significant differences between the PCI and CABG groups in the 3-year rates of the primary endpoint in patients with versus without baseline LLT ( P interaction =0.62). Among patients with baseline LLT, the 3-year rate of ischemia-driven revascularization was higher after PCI compared with CABG (13.7 vs. 5.3%; adjusted hazard ratio=2.97; 95% confidence interval: 1.95–4.55; P <0.0001), in contrast to patients without baseline LLT (9.8 vs. 12.1%; adjusted hazard ratio=0.79; 95% confidence interval: 0.47–1.33; P =0.39) ( P interaction =0.0003). Conclusion: In the EXCEL trial, 3-year major adverse event rates after PCI versus CABG for LMCAD were similar and consistent in patients with and without LLT at baseline; however, revascularization during follow-up was more common after PCI compared with CABG in patients with baseline LLT, but not in those without baseline LLT. Abstract : Supplemental Digital Content is available in the text.